2008
DOI: 10.1016/j.bandl.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effective brain connectivity in children with reading difficulties during phonological processing

Abstract: Using Dynamic Causal Modeling (DCM) and functional magnetic resonance imaging (fMRI), we examined effective connectivity between three left hemisphere brain regions (inferior frontal gyrus, inferior parietal lobule, fusiform gyrus) and bilateral medial frontal gyrus in 12 children with reading difficulties (M age = 12.4, range: 8.11-14.10) and 12 control children (M age = 12.3, range: 8.9-14.11) during rhyming judgments to visually presented words. More difficult conflicting trials either had similar orthograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
116
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 45 publications
20
116
4
Order By: Relevance
“…The rhyme (identification and production) was selected from among the phonological skills to compose the "Phonological awareness" subtest, as studies show that this ability develops early in children with typical development (Cao, Bitan, & Booth, 2008;Pessoa & Paes, 2005), which does not occur in children with dyslexia (Lima et al, 2008;Salgado & Capellini, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The rhyme (identification and production) was selected from among the phonological skills to compose the "Phonological awareness" subtest, as studies show that this ability develops early in children with typical development (Cao, Bitan, & Booth, 2008;Pessoa & Paes, 2005), which does not occur in children with dyslexia (Lima et al, 2008;Salgado & Capellini, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a previous effective connectivity (fMRI) study, it was shown that this same region was acting as a mediator of information trafficking to those two pathways, and thereby optimizing reading performance (Levy et al, 2009). Other connectivity studies also highlight the role of these pathways during reading (Cao et al, 2008;Richardson et al, 2011). In the major endeavor of comprehending the complex neural dynamics sustaining reading, these findings propose that future studies should take particular note of the forward and backward connections emanating from the LOT towards the ventral and dorsal pathways.…”
Section: Scalp Topographies and Brain Views (Sagittal And Axial Planementioning
confidence: 99%
“…Multiple imaging studies have reported hypoactivation in children and adults with dyslexia during reading-related tasks, especially those that demand phonological analysis of print, in left parietotemporal and occipitotemporal regions (9)(10)(11)(12)(13)(14)(15)(16)(17). Many studies have also reported hyperactivation in dyslexia, most often left and right inferior frontal gyri (IFG) (10,12,(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%